A comparative study of Mexican and Irish compliment responses - Flores-Salgado, Elizabeth; Witten, Michael T. (Colombian Applied Linguistics Journal, 2019)
The purpose of the present study is to compare the compliment responses (CRs) provided by 60 native Mexican Spanish speakers and 60 Irish English native speakers. Using a discourse completion task, 1080 responses were analyzed based on Herbert’s (1989) and Nelson, El Bakary and Al-Batal’s (1993) taxonomy. Findings suggest the existence of cross-cultural similarities in Irish and Mexican CRs in the frequency of deflecting comments and the mechanisms that are used to redirect the praise force. Second, the two languages differ in important ways. In responding to compliments, Irish recipients are much more likely than Mexican speakers to use a single strategy when formulating CRs. The findings further show that social factors (social distance, social power, gender, and the topic of the compliment) in both Mexican and Irish society seem to be crucial parameters in the formulation and acceptance or rejection of a compliment.